Enhancing SIM Card Technology: Developing an Advanced Operating System - Kose, Busra Ozdenizci; Sardag, Alp; Coskun, Vedat; Mantar, Ali (Видавництво Львівської політехніки, 2023)
The emergence of smart cards is a significant achievement in the field of information technology. They are growing in importance as they offer secure data storage and authentication, improve security, simplify processes, reduce costs, and have a variety of applications. In particu- lar, nowadays SIM cards play a vital role in the Telecom industry as an important type of smart card that allows a user to make calls, send messages, store details such as phone number and network authentication information, and provide various mobile data services. Currently, some leading companies take advantage of having their own smart card operating systems and have significant impact on the market on various issues (hardware on which the smart card operating system will run; security restrictions; control, permission and control of any application, etc.). It is important to work on creating a more flexible, adaptable and secure operating system infrastructure in order to overcome these limitations both in the customer perspective and in the ecosystem. The purpose of this research is to introduce the creation of a special Java Card operating system designed for SIM cards used in the Telecom industry. The study presents the software requirements and development steps of the proposed operating system and innovative architectural components necessary for its operation as a SIM card beyond being a Java Card operating system. The proposed new Java Card based SIM operating system is expected to pave the way for the development of eSIM operating system infrastructure as well as 5G tech- nology and offer valuable opportunities.
Keywords: smart card; SIM; Java card; operating system; system architecture